Nutrition Counseling Need in Burn Patients (Majalah Kedokteran Bandung, 2020)
Burns can increase metabolic responses of the sufferers, making adequate nutrition important for burn patients and needs to be considered in the management of burns. Counseling on the importance of nutrition for burn patients can reduce the risk of burn complications. This study was an intervention study designed to increase the community's knowledge and awareness of the importance of nutrition in burn patients. In this study, a lecture session and discussion session on nutrition in burn patients were held by the Division of Plastic Surgery, Department of Surgery, Dr. Hasan Sadikin General Hospital, Bandung, Indonesia at the Jatinangor Public Health Center, Sumedang, Indonesia, on August 14, 2019. Of all participants attending this event, thirty-one participants who participated in through the whole agenda of this event were sampled to be the respondents. Data were collected using a pre- and post-test questionnaires consisting of items on basic knowledge, first treatment, and nutrition for burn patients. More women (74%) participated in this study. Most respondents were over 40 years old (39%) and graduated from senior high school (39%). There was a significant increase in knowledge of the respondents before and after counseling the nutrition of burn patients (p
Keywords: Burns; Health Promotion; Knowledge; Nutrition